Pengembangan Video Animasi untuk Tema “Wie Die Zeit Vergeht” pada Mata Kuliah Sprechen A2 - Yeni Fadilah Hizriana Damanik (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The purpose of this study was to create an animated video as a learning media for the theme "Wie die Zeit vergeht" in the Sprechen A2 subject with the Flipaclip application and the application of the 4D development model from Thiagarajan. The steps of this development model are: (i) the definition stage, (ii) the planning stage, (iii) the creation stage, and (iv) the dissemination stage. This learning media was developed based on the Kursbuch Netzwek A2 book. This research was conducted at the Language Laboratory of the Faculty of Languages ​​and Arts, State University of Medan. The result of this creation is an animated video made with Flipaclip. This animated video was validated by material experts and media experts. The material validator gave a score of 85 (good) and the media validator gave a score of 90 (good). Based on the evaluation of the experts, it can be concluded that the animated video with the topic "Wie die Zeit vergeht" is feasible and can be used for the Speaking A2 course.